Study of Risk Mitigation Strategies in the PPP Flyover Project Sitinjau Lauik 1 (Bina Marga – PT. Hutama Panorama Sitinjau Lauik) - Suci Yolanda; Gina Cynthia R. Hasibuan; M. Ridwan Anas (Green Publisher Indonesia, 2026)
Infrastructure projects implemented under the Public–Private Partnership (PPP) scheme have a high level of risk complexity due to the long-term division of technical, operational, and occupational safety responsibilities. The Sitinjau Lauik 1 Flyover project is characterized by extreme topography, landslide potential, and heavy equipment mobilization, all of which increase the likelihood of construction and occupational safety risks. This study aims to analyze the influence of risk mitigation strategies on construction risk control in PPP projects. The research method employs a descriptive quantitative approach based on the frameworks of ISO 31000 and SMK3, as well as Failure Mode and Effects Analysis (FMEA), using severity, occurrence, and detection parameters to obtain the Risk Priority Number (RPN). The results indicate that there are 31 primary risks, with the highest priority levels originating from technical aspects in the field, such as heavy equipment accidents, potential landslides, inconsistencies in construction methods, and risks associated with working at elevation. The mitigation strategies implemented—including improvements in work methods, periodic inspections, enhancement of workforce competence, and strengthening of the supervision system—have been proven to reduce risk levels from high to medium and low categories. The study concludes that the systematic implementation of risk mitigation strategies has a significant effect on reducing construction risk levels and improving the safety and performance of PPP projects.